2018
DOI: 10.1371/journal.pone.0199924
|View full text |Cite
|
Sign up to set email alerts
|

Personality and social support as determinants of entrepreneurial intention. Gender differences in Italy

Abstract: The interest in the promotion of entrepreneurship is significantly increasing, particularly in those countries, such as Italy, that suffered during the recent great economic recession and subsequently needed to revitalize their economy. Entrepreneurial intention (EI) is a crucial stage in the entrepreneurial process and represents the basis for consequential entrepreneurial actions. Several research projects have sought to understand the antecedents of EI. This study, using a situational approach, has investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
4
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 83 publications
(154 reference statements)
11
66
4
8
Order By: Relevance
“…No difference with respect to the internal locus of control was also proven by the Mueller (2004) study across the entire sample of seventeen countries. On contrary, Molino et al (2018) study on personality found higher levels of self efficacy and internal locus of control in males. Carland and Carland (1991) study investigated personality traits (preference for innovation, propensity for risk taking and need for achievement) among entrepreneurs and managers, and found no difference in personality traits between female and male entrepreneurs, that were stronger than in managers.…”
Section: Psychological/personality Traits Of Entrepreneursmentioning
confidence: 78%
See 1 more Smart Citation
“…No difference with respect to the internal locus of control was also proven by the Mueller (2004) study across the entire sample of seventeen countries. On contrary, Molino et al (2018) study on personality found higher levels of self efficacy and internal locus of control in males. Carland and Carland (1991) study investigated personality traits (preference for innovation, propensity for risk taking and need for achievement) among entrepreneurs and managers, and found no difference in personality traits between female and male entrepreneurs, that were stronger than in managers.…”
Section: Psychological/personality Traits Of Entrepreneursmentioning
confidence: 78%
“…intentions, opportunity recognition, strategies, decision making, success). Molino et al (2018) have tested personality and social support as determinants of entrepreneurial intention in the Italian context and found that men scored higher levels of self-efficacy and internal locus of control than women. These findings are not in line with the present research, as it has not been found any statistically significant difference among women and men with respect to self-efficacy and externalization as opposite of internal locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions aimed at enhancing employability are linked to issues of strengthening entrepreneurial intention, or paths to enhancing the achievement of objectives, and are attentive to gender differences and socio-economic origin (Molino et al 2018;Ojala et al 2019). Although these are useful, they should be balanced with important socio-political actions to effect employment and-with a massive education and training of the Italian leadership-aimed at affecting entrepreneurial and managerial cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no clarification of the type of entrepreneurs that may be found (Hsieh & Wu, 2019). Along these lines, there are other variables that may be considered such as entrepreneurial intent (Hu, Wang, Zhang, & Bin, 2018;Molino, Dolce, Cortese, & Ghislieri, 2018;Newman et al, 2019), dissatisfaction with the current job (Sousa, Araújo, Lua, & Gomes, 2019), and emotional regulation (Castellano, Muñoz-Navarro, Toledo, Spontón, & Medrano, 2019). It is well known that using self-reports leads to many limitations such as acquiescence bias and social desirability bias (Navarro-González, Lorenzo-Seva, & Vigil-Colet, 2016).…”
Section: Discussionmentioning
confidence: 99%